A study of prognostic factors in cutaneous malignant melanoma - Sasikumar, M. N.; Kurian, Annie Sandhya (International Surgery Journal, 2019)
Background: Melanocytes are cells of neural crest origin that migrate principally to basement membrane of skin at dermo-epidermal junction. These cells when exposed to carcinogens result in malignant melanoma. Melanoma accounts for only 4% to 5% of all skin cancers but causes majority of deaths from skin cancers. Several factors affect its prognosis. Most reports agree that tumour thickness is the most important factor, but several others also interact. Methods: From the department of Medical College, Kottayam the cancer of patient who had histopathologically proven malignant melanoma during 2008-2012 were obtained from this HPR, details of the lesion such as Breslows thickness, level of invasion, presence of ulceration, mitoses, lymphocytic infiltration, tumor vascularity etc. were recorded. The case records of the some patients were then obtained from the record library, from which the clinical details of the lesions and follow up were recorded. These patients were followed till 2013. The significance and each of these factors were these analysed. Results: There were a total of 64 cases with equal gender distribution. The incidence reflected the global trend of increasing number of cases. The factors which affect prognosis included nodal status, thickness, level of invasion, ulceration, mitoses, lymphocyte infiltration, vascularity and lymphovascular emboli. A striking finding was most of the patients presented at an advanced stage, unlike the West. Conclusions: Malignant melanoma is a deadly disease especially when diagnosed late. Many factors in addition to thickness were found to have prognostic significance.